Differences in Mechanical Reasoning of Engineering Students - MS, Firdaus; Saud, Eddy (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
This study aims to analyze the differences in engineering aptitude-mechanical reasoning among engineering students. This study is a quantitative study with a cross-sectional study design. This study was conducted at the Faculty of Engineering, Ogan Komering Ilir Islamic University, Kayuagung (UNISKI). The subjects of this study were selected by simple random sampling so that the number of samples obtained was 26 students of the mechanical engineering study program and 36 students of the civil engineering study program. The instrument used in this study was the aptitude-mechanical reasoning test developed by Mackellar (2015). This instrument consists of several topics, namely 1) Levers, 2) Pulleys, 3) Gears, 4) Springs, 5) Simple electrical circuits, and 6) Tools. The research data were analyzed using the RASCH Model Analysis using the WINSTEP application. The results showed no significant difference between mechanical engineering and civil engineering study programs in pulleys, springs, and electrical circuits. In the element of levers, gears and tools, the t count value is greater than the t table, so there is a significant difference between mechanical engineering and civil engineering study programs.